Prolegomena to the history of Israel: with a reprint of the article ‘Israel' from the Encyclopaedia Britannica - Wellhausen, Julius (Cambridge library collection. Religion, 2013)
Julius Wellhausen (1844–1918) first published this work in German in 1878. Reissued here is the 1885 English translation of a revised 1883 version. Intended as a multi-volume work, this first book now stands as a self-contained work. A biblical scholar and orientalist, Wellhausen was professor of theology at Greifswald (until resigning for reasons of conscience) and then professor at Halle, Marburg and Göttingen. An early exponent of scientific philology, he placed the Pentateuch in a historical-social context, setting aside theological traditions. In this work, he sets out his method and argues that the Pentateuch is a synthesis of four independent narratives. He then examines the history of worship, sacrifice, sacred feasts, priests, and the law in ancient Israel. Wellhausen is a central figure in modern biblical studies, his theory dominated scholarship for a century, and his pioneering work remains of great interest in the field.